28y=39(9y-6)

Simple and best practice solution for 28y=39(9y-6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 28y=39(9y-6) equation:


Simplifying
28y = 39(9y + -6)

Reorder the terms:
28y = 39(-6 + 9y)
28y = (-6 * 39 + 9y * 39)
28y = (-234 + 351y)

Solving
28y = -234 + 351y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-351y' to each side of the equation.
28y + -351y = -234 + 351y + -351y

Combine like terms: 28y + -351y = -323y
-323y = -234 + 351y + -351y

Combine like terms: 351y + -351y = 0
-323y = -234 + 0
-323y = -234

Divide each side by '-323'.
y = 0.7244582043

Simplifying
y = 0.7244582043

See similar equations:

| 2.94x^2-24.99x-13.23=0 | | (63x^9)/9 | | 5y+1.8-4y=-3.2 | | x=2.5+3y | | x-3+4x=-7x-5x | | 8x-4y-2y+7x+10= | | 0.2(30)=0.4(50+x)-0.8x | | 2/3(8+4x)=104/3 | | 1/7x+3/4x | | 3/5x=1/2x+2 | | b+4b+8=16b+4 | | 4/5n+3-2/3n=1/2-3n | | 8(x+1)-(5x-1)=1 | | X^6+36=100 | | 2x^2-2=7x | | .5y+.5-y=.25 | | X(x)+10x+25=36 | | 7(x+5)-(4x-1)=2 | | 25x^2-20x+4=25 | | 9t+t= | | 3(x-3)=13x-21 | | 8(x+5)-(3x-5)=7 | | 12n+8=11 | | -3x+8x-2= | | 3x^4=24 | | 2x+38-3x=1-9x+5 | | 12d+11=27 | | 2x^2-1=8x | | 9(x-2)=-36 | | 0.5x-0.3(2-x)=4.2 | | 6.5/3x+5=11 | | -d+43-2d=9 |

Equations solver categories